#import "@youwen/zen:0.1.0": * #import "@preview/mitex:0.2.5": * #show: zen.with( title: "Homework 3", author: "Youwen Wu", ) #set heading(numbering: none) #set par(first-line-indent: 0pt, spacing: 1em) #let nonzero = $ZZ_(!=0)$ Problems: 1.5: $hash$ 3cdefgh, 4de, 6de, 7ab, 9, 10, 11, 12a 1.6: $hash$ 1bd, 4abcd, 6abefik 2.1: $hash$ 4, 5, 6abcd, 8, 11ab, 14ab, 15abcd = 1.5 *3c.* If $x^2$ is not divisible by 4, then $x$ is odd. #proof[ Suppose $x$ is not odd. We seek to show that $x^2$ is divisible by $4$. Then $x$ is even and $exists k in ZZ_(!=0), x = 2k$. Thus $x^2 = 4k^2$, which implies $4 | x^2$. So $x$ is not odd implies $x^2$ is divisible by 4, and therefore the contrapositive (which is our original statement) is also true. ] *3d.* If $x y$ is even, then either $x$ or $y$ is even. #proof[ Suppose that $not (x "or" y" is even")$. In other words, $x$ and $y$ are both odd. We seek to show that $x y$ is odd. Then $exists j,k in ZZ_(n!=0), x = 2j + 1, y = 2k + 1$. So $x y = 4 j k + 2j + 2k + 1 = 2 (2 j k + j + k) + 1$ where $2 j k + j + k$ is an integer so $x y$ is odd. This is the contrapositive, so the original statement is also true. ] *3e.* If $x + y$ is even, then $x$ and $y$ have the same parity. #proof[ Suppose $x$ and $y$ had different parities. We seek to show that $x + y$ is odd. Without loss of generality, let us inspect the case where $x$ is odd. Then $y$ must be even and $ exists j,k in ZZ_(!=0), x = 2j + 1, y = 2k \ x + y = 2j + 1 + 2k = 2(j + k) + 1 = 2n + 1, n in ZZ_(n!=0) $ Repeat the same reasoning for when $x$ is even and $y$ is odd. We've shown that $x$ and $y$ having different parities implies that $x + y$ is odd. Therefore the contrapositive is also true. ] *3f.* If $x y$ is odd, then both $x$ and $y$ are odd. #proof[ Suppose that both $x$ and $y$ are odd was not true, in other words $x$ or $y$ are even (here or is the logical $or$). We seek to show that this implies $x y $ is even. Then we have two cases: either $x$ or $y$, but not both, are even, and the case where $x$ and $y$ are both even. We look at the first case, without loss of generality, assume $x$ is even and $y$ is odd. Then $ exists j,k in ZZ_(!= 0), x = 2j, y = 2k + 1 \ x y = 2j(2k + 1) = 4 j k + 2j = 2(2 j k + j) = 2n, n in ZZ_(!=0) $ So $x$ and $y$ having different parities implies $x y$ is even. The argument holds identically when instead $y$ is even and $x$ is odd. Now we turn our attention to the case when $x$ and $y$ are both even. Then $ exists j,k in ZZ_(!=0), x = 2j, y = 2k \ x y = 2j dot 2k = 4 j k = 2 (2 j k) = 2n, n in ZZ_(!=0) $ So this also implies that $x y$ is even. Therefore $x$ or $y$ being even indeed implies $x y$ is also even, and the contrapositive is also true. ] *3g.* If 8 does not divide $x^2 - 1$, then $x$ is even. #proof[ Suppose that $x$ is odd. We seek to show that 8 does in fact divide $x^2 - 1$. $ exists k in nonzero, x = 2k + 1 \ x^2 - 1 = 4k^2 + 4k = 4(k^2 + k) $ Now we need to see if it's divisible by 8. First consider the unique case $k = 0$, where $x^2 - 1 = 0$. Clearly $8 | 0$ so 8 does divide $x^2-1$. Now we consider all other values. Notice that for all other possible values of $k$, $k^2 + k$ is greater than 1. We see this by noting that $k^2 + k$ is a quadratic with its absolute minima at $k = 1/2$, therefore we can check the two non-zero integers closest to this value. For $k = 1$, $k^2 + k = 2$. Since we already checked $k=-1$, let's check $k=-2$, which gives $k^2 + k = 2$. For all values of $k$ greater than 1 or less than $-2$, $k^2 + k$ must be greater than 2 (because it's a quadratic). Therefore $4(k^2 + k)$ can be written as $8n$ for some integer $n$, so 8 indeed divides $x^2 - 1$ for all possible $k$, and the contrapositive is also true. ] *3h.* If $x$ does not divide $y z$, then $x$ does not divide $z$. #proof[ Assume $x$ does divide $z$. We seek to show that $x$ does divide $y z$. If $x | z$ then $exists k in nonzero, k x = z$. So $y z$ can be written as $y k x$. But this shows $exists j in nonzero, j x = y z$, namely $j = y k$, which means $x | y z$, and the contrapositive is also true. ] *4d.* If $(x+1)(x-1) < 0$, then $x < 1$. #proof[ Suppose that $x >= 1$. We seek to show that $(x+1)(x-1) >= 0$. Expanding out factors, $ (x+1)(x-1) = x^2 - 1>= 0 $ This quadratic is zero at exactly $x = 1$ and positive for all $x > 1$. So it's true for all possible values of $x$. Therefore our original statement is also true. ] *4e.* If $x(x-4) > -3$, then $x < 1$ or $x > 3$. #proof[ Suppose that $x >= 1$ and $x <= 3$. We seek to show $x(x-4) <= -3$. Expanding out factors, $ x(x-4) = x^2 - 4x > -3 $ This quadratic has its stationary point at $x = 2$. Let's check its value at $x = 1$ and $x = 3$. At $x = 1$, $x(x-4) = -3$. So for all values greater than 1 until $x = 2$, $x^2 - 4x$ is less than $-3$. Our inequality is satisfied. At $x = 3$, $x(x-4) = -3$ again. So for all values less than 3 until $x = 2$, $x^2 - 4x$ is less than $-3$. Our inequality is satisfied for both $x >=1$ and $x <=3$, so $x^2 -4x > -3$ is true for all possible $x$ and the contrapositive is also true. ] *6d.* If $a - b$ is odd, then $a + b$ is odd. #proof[ Suppose, seeking a contradiction, that if $a - b$ is even, then $a + b$ is odd. Then $exists k in nonzero, a - b = 2k$. Which means we can write $a + b = 2k + 2b$. But we can factor this as $2(k + b)$ and so $a + b = 2n, n in nonzero$, implying it is even. However we assumed that $a + b$ should be odd, a contradiction. Therefore $a - b$ must be odd. ] *6e.* If $a < b$ and $a b < 3$, then $a = 1$. #proof[ Suppose, seeking a contradiction, that $a >= b$ and $a b >= 3$ implies $a = 1$. Consider the specific cases $a = b$, $a b = 3$. Then $a = 3/a$, and $a = plus.minus sqrt(3)$. However we assumed $a = 1$ is implied, a contradiction. Therefore we must have $a < b$ and $a b < 3$. ] *7a.* $a c$ divides $b$ and $b$ divides $b + 3$ if and only if $a = 2$ and $b = 3$. We first show the result left to right, namely, $a c | b c => a | b$. $ exists k in nonzero, k a c = b c \ k a = b $ which is the definition of $a | b$. Now we show the right to left direction, namely, $a | b => a c | b c$. $ exists k in nonzero, k a = b \ k a dot c = b dot c $ So $a c | b c$ by the definition of divisibility. Therefore the biconditional is true, as we have shown both directions. *7b.* The right to left direction is very easy in this case. By directly plugging in $a = 2$, $b = 3$, we see that $2 + 1 | 3$ and $3 | 3 + 3$. To show the left to right case, *9.* #proof[ Suppose that instead $n/(n+1) <= n/(n+2)$. We can be assured the following operations do not flip the inequality as $n$ cannot be negative. $ n(n+2) <= n(n+1) \ n + 2 <= n + 1 \ 2 <= 1 $ So $n/(n+1) > n/(n+2)$. ] *10.* #proof[ Suppose that $sqrt(5)$ was rational. That is, $sqrt(5) = p/q$ for nonzero integers $p$ and $q$. Additionally, assume that $p/q$ is in its most reduced form, that is, $p$ and $q$ share no common factors besides 1. Then $ p^2 = 5q \ $ implies that $ 5 | p^2 $ We need to show that $5 | p^2 => 5 | p$. By the fundamental theorem of arithmetic, $p^2$ has 5 as one of its unique prime factors. If 5 was not a factor of $p$, then $p^2 = p dot p$ would not have 5 in its factors either. So 5 is a factor of $p$ and thus $5 | p$. Note that 5 appears at least twice amongst the prime factors of $p^2$. Then $5q$ should also have at least two 5s in its prime factorization. Then $q$ has at least one 5 in its prime factorization. However we assumed that $p$ and $q$ share no common factors besides 1, so this is a contradiction. Therefore $sqrt(5)$ is not rational. ] *11.* #proof[ We say that two numbers $x$ and $y$ are within $1/2$ unit from one another if $|x - y| < 1/2$. Consider the distance between $z$, and $y$, if it is within $1/2$, then we are done. Otherwise $z - y >= 1/2$. We know that $ (1 - z) + x + (y-x) + (z-y) = 1 $ because this is the length of all the line segments partitioned by $x,y,z$, which is the interval 1. If $(z - y) >= 1/2$, then everything else must be less than $1/2$. So the maximum value of $y-x$, the distance between $x$ and $y$, is less than $1/2$. Therefore either $y$ and $z$ are within $1/2$ unit of each other or $y$ and $x$ are. ] *12a.* F. This is a proof that $not A => B$ is a contradiction, which is not sufficient to show $A => B$. = 1.6 *1b.* #proof[ Consider $m = 1$, $n = -1$. Then $15(1) + 12(-1) = 3$. ] *1c.* Rewrite $2m + 4n = 7$ as $2(m + 2n) = 7$. Notice that $2(m + 2n) = 2k, exists k in nonzero$ and therefore is an even number for any $m$, $n$. But 7 is not even. So no choices of $m$ and $n$ can create a number equal to 7. So no $m$ or $n$ exists. *4a.* #proof[ Consider $x = 2$. Then $x^2 + x + 41 = 46$, which is not prime. So it's false. ] *4b.* #proof[ For any $x$, choose $y = -1 dot x$. Then $x + (-x) = x(1 - 1) = 0x = 0$. This is also trivially true when considering our usual field of reals because the existence of $y$ such that $x + y = 0$ is an axiom. ] *4c.* Consider $x = 2$ and $y = 1$. Then $1 > 2$ is false. *4d.* Consider $a = 10$, $b = 2$, $c = 5$. Then $a | b c$ because $10 | 2 dot 5$ but 10 does not divide either 2 or 5. *6a.* #proof[ Rewriting the inequality, $ 1 / n <= 1\ 1 <= n $ This is true for all $n in NN$ by the definition of $NN$. ] *6b.* #proof[ Rewriting, $ 1 / n < 0.13 \ 1 < 0.13n \ n > 1 / 0.13 $ So such an $M$ is $1/0.13$, because all naturals greater than $1/0.13$ are greater than $1/0.13$. ] *6e.* #proof[ $ forall n in NN, n + 1 > n $ ] *6f.* $ forall k in ZZ, m = -k, k + m = 0 \ forall n in NN, 0 <= 0 < n $ *6i.* First consider $K = 10$, and therefore $ forall r > 10, r^2 > 100 $ Then note that our inequality is equivalent to $r^2 > 100$, which is true for all $r$. $ 1 / (r^2) < 0.01 \ r^2 > 100 \ $ So a $K$ exists, namely $K = 10$. *6k.* Consider $M = 51$. Then $forall r > 51, 2r > 102$ and $2r > 100$ is always true. $ 1 / (2r) < 0.01 \ 2r > 100 $ So such an $M$ exists, namely, $M = 51$. = 2.1 *4a.* False. *4b.* True. *4c.* False. *4d.* True. *4e.* True. *4f.* False. *4g.* True. *4h.* False. *4i.* False. *4j*. True. *5a.* True. *5b.* True. *5c.* True. *5d.* True. *5e.* False. *5f.* True. *5g.* True. *5h.* True. *5i.* False. *5j.* True. *5k.* True. *5L.* True. *6a.* $ A = {1,2}, B = {1,2,3}, C = {1,2,4} $ *6b.* $ A = B = C $ A particular example might be $A = {1}, B = {1}, C = {1}$. *6c.* $ A = {1}, B = {1,2}, C = {3} $ *6d.* $ A = {1,2}, B = {1,2,3}, C = {5,6,7} $ *8.* Theorem 2.1.1: $forall A, B, C, A subset.eq B and B subset.eq C => A subset.eq C$. #proof[ $ forall a in A, a in B \ forall a in A, exists b in B, a = b \ forall b in B, b in C \ forall a in A, a in C => A subset.eq C $ ] *11a.* #proof[ $ {x in RR : 3 / 4 x - 2 > 10} \ = {x in RR : x > 16 } \ = (16, infinity) $ ] *11b.* #proof[ $ {x in RR : |x - 4| = 2|x| - 2} \ = {x in RR : |x - 4| = 2|x| - 2} \ $ Now we consider various cases. Consider $x >= 4$. Then $ {x in RR : x - 4 = 2x - 2} \ = {x in RR : x - 4 = 2x - 2} \ = {x in RR : x = -2} \ $ But in this case $x >= 4$. Since there is no $x >= 4$ such that $x = -2$, this is actually $emptyset$. Now consider $0 <= x < 4$. $ {x in RR : 4 - x = 2x - 2} \ = {x in RR : x = 2} \ = {2} $ Now consider $x < 0$. Then $ {x in RR : 4 - x = -2x - 2} \ {x in RR : x = -6} $ So the set contains $6$ when $x < 0$. And since these inequalities span all $x in RR$, the only members of the set are ${2, -6}$. ] *11c.* #proof[ $ {x in RR : 2|x+3| + x = 0} $ For $x >= -3$, we have $ {x in RR : 2(x + 3) + x = 0} \ = {x in RR : x = -2} \ = {-2} $ For $x < -3$, we have $ {x in RR : 2(3 - x) + x = 0} \ = {x in RR : x = 6 } \ = {6} $ And since these inequalities partition $RR$ the original set is ${-2, 6}$. ] *11d.* $ {x in RR : |x| = 6 - |2x|} $ Consider $x >= 0$. Then $ {x in RR : x = 6 - 2x} \ = {x in RR : x = 2} $ Consider $x < 0$. Then $ {x in RR : -x = 6 + 2x} \ = {x in RR : x = -2} $ So $ {x in RR : |x| = 6 - |2x|} = {-2, 2} $ *11e.* $ {x in RR : |x + 3| <= -4x - 2} $ Consider $x >= -3$. Then $ {x in RR : x <= -1} \ = (-infinity, -1] $ Now consider $x < -3$ Then $ {x in RR : 3 - x <= -4x - 2} \ = {x in RR : x <= -5 / 3} \ = (-infinity, -5 / 3] $ But $(-infinity, -5/3) union (-infinity, 1] = (-infinity, 1]$ so that is our answer. *11f.*